Empowering 8: the Information Literacy model developed in Sri Lanka to underpin changing education paradigms of Sri Lanka - Wijetunge, Pradeepa (My University, 2005)
Information literacy (IL) is the ability to identify, locate, evaluate, organize and effectively create, use and communicate information to address an issue or a problem. It is a basic human right to lifelong learning. Information itself is becoming a transforming strategic resource of the emerging information society. Without information literacy, the information society will not be able to achieve its full potential. Therefore, the concept and practice of information literacy must be promoted from an early age among the school going children. Information literacy is more relevant for the developing nations to enable themselves to bridge the growing info-divide between the developed and the developing nations. In this context, a regional workshop was organized by NILIS to create awareness of information skills for learning among the participants from South and Southeast Asian countries. Empowering Eight (E8), an Information Literacy Model was developed at this workshop organized jointly by IFLA-ALP and the National Institute of Library & Information Sciences (NILIS) of Sri Lanka. There were participants representing ten South and Southeast Asian countries. The objective of the workshop was to enhance the resource-based learning in these countries by sensitizing the participants to Information Literacy, which as a concept has not taken roots in majority of the countries in the region. When a plethora of IL models are already available, one may question why the wheel is being re-invented. Re-inventing the wheel or developing another model is essential because of the composite culture and local conditions in these countries. If an existing model used in a developed country is imposed, it would be difficult for the stakeholders to understand the philosophical roots behind the model. Therefore, the workshop participants, throughout five days worked from identifying the need of IL through comparison of different models to building the E8 to suit the local needs of the region. This paper will discuss in detail the Empowering 8 model and its application and implementation in the Sri Lankan context.